The Commonwealth Caribbean COVID-19: Regions Resilient Pathway During Pandemic - Umakanthan, Srikanth; Bukelo, Maryann M.; Gajula, Somu Sekhar (Frontiers in Public Health, 2022)
The coronavirus disease (COVID-19) has created severe humanitarian and socio-economic constrains in the world. The health crises caused by COVID-19 has focused on consistent co-operation and strong bonding between the developed, developing and the under-developed countries to overcome this challenging pandemic.